Kajian Bentuk Rumoh Aceh Di Desa Rumpet - Yulia. R; Zia Faizurrahmany El Faridy (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2025)
Rumoh Aceh is a traditional building that is one of the cultures and identities of Aceh. Partly in Rumpet Village, Aceh Besar Regency, there are several Acehnese houses that are still being lived in. Rumoh Aceh in Rumpet Village totals 9 units, and all of them are occupied as residential houses. The problem in this research is how the shape change and typology of the form of Aceh rumoh in Rumpet Village.